Analisis Genetik Gen Protective Antigenic pada Bacillus anthracis Isolat Jawa Tengah dan Yogyakarta (GENETIC ANALYSIS ON PROTECTIVE ANTIGENIC GENE OF BACILLUS ANTHRACIS ISOLATES OF CENTRAL JAVA AND YOGYAKARTA) - Sanam, Maxs Urias Ebenhaizar; Asmara, Widya; Wahyuni, Agnesia Endang Tri Hastuti; Wibowo, Michael Haryadi (Jurnal Veteriner, 2015)
The aim of the study was to determine sequence and genotype diversity of protective antigenic gene ofBacillus anthracis isolated from Central Java and Yogyakarta. Pag-A gene which encodes for antigenicprotein is one toxin component and the virulent factor of B. anthracis. As many as five isolates fromSemarang, Sragen, and Boyolali (Central Java) and Sleman (Yogyakarta) were used. The gene wassequenced and amplified used three set of primers PA1857/PA2436, PA8/PA5, and PA-5F/PA-5R. Theresult showed that the nucleotide sequences of gene from five isolates were identical and only had onenucleotide difference as compared to B. anthracis sterne M22589. All isolates were confirmed as genotypebased on pag-A sequence. It was concluded that all B. anthracis from Central Java and Yogyakarta haveidentical pag-A sequence and belong to genotypt-1. Further studies are needed to investigate B. anthracisisolates from other regions of Indonesia.
Keywords: pagA, genotype, protectiveantigenic, Bacillus anthracis